Neutrophil to lymphocyte and monocyte to high-density lipoprotein ratios are promising inflammatory indicators of bipolar disorder. (3rd January 2023) - Kulacaoglu, Filiz; Yıldırım, Yusuf Ezel; Aslan, Metin; İzci, Filiz
Abstract: Aims: The neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), monocyte to lymphocyte ratio (MLR), and monocyte to high-density lipoprotein (MHR) are indicators of inflammation. In this study, we aimed to examine the possible association between NLR, PLR, MLR, and MHR in the same patients with bipolar disorder (BD) during their manic, depressive, and euthymic episodes. Methods: The participants of this study consisted of 61 patients with BD, aged between 18 and 65, who were hospitalized with a diagnosis of BD. Patients who were hospitalized during their manic and depressive episodes and medication free for at least 1 month before hospitalization were included. White blood cell, neutrophil, lymphocyte, platelet, and monocyte counts, high-density lipoprotein (HDL) cholesterol, and C reactive protein (CRP) levels were recorded. Results: Leukocytes ( p = 0.000), neutrophil ( p = 0.009), monocyte counts ( p = 0.012), CRP levels ( p = 0.026), NLR ( p = 0.025), and MHR ( p = 0.011) values were significantly higher in their manic episode and depressive episode compared with the values in their remission period. There was no significant difference between manic and depressive episodes in terms of inflammation parameters. Significant positive correlations were found between the number of depressive episodes and patients' CRP levels ( p = 0.031). Conclusions: This study was the first study to examine the inflammatory markers such as NLR, MLR, PLR, and MHR levels in same patients with BD during their three episodes of disorder. Both NLR and MHR values in manic and depressive episodes were higher than euthymic episodes. NLR and MHR were useful inflammatory markers to evaluate inflammation in bipolar patients.